Sierra Leone Economic Update, June 2020 : The Power of Investing in Girls - World Bank (World Bank, Washington, DC, 2020)
Sierra Leone, like many countries in the world, is now facing the dire human and economic impacts of the COVID-19 (Coronavirus) pandemic. Prior to the COVID-19 (Coronavirus) crisis, Sierra Leone was one of the fastest growing countries in Africa. However, growth prospects have been severely undermined since the COVID-19 (Coronavirus) outbreak. The COVID-19 (Coronavirus) crisis, like the 2014–2015 Ebola epidemic, is likely to damage adolescent girls’ education prospects and their human capital potentials as the prevalence of child marriage and early childbearing as well as the risk of girls dropping out of school are all exacerbated during crises. This update comprises the economic outlook for Sierra Leone and a special chapter on educating girls. First part discusses recent economic developments, the impact of COVID-19 (Coronavirus) on the economy and the growth prospects under different scenarios regarding the spread of COVID-19 (Coronavirus). It discusses the potential channels of transmission, provides estimates of spillovers, and emphasizes necessary policy responses. Second part of this update highlights the economic gains that could be achieved from ending child marriage and promoting girls’ education. It also discusses a range of measures that could be undertaken by the government following the recent decision to allow pregnant girls to stay in school or return to school.